Recognizing Madrasah Aliyah Amaliah Sunggul Communication Climate In Developing Teacher Competencies - Fauzan Ahmad Siregar; Lailatul Usriyah (The Faculty of Education and Teaching Training, 2023)
Abstract Achieving the vision and mission of the madrasah is determined by various aspects including teacher competence. Therefore, developing teacher competencies that are managed effectively is a logical thing in an effort to achieve the vision and mission of the madrasah. Various educational institutions still experience obstacles in efforts to develop teacher competence, so this has an impact on the quality of education. The purpose of this study is to describe how the management process of teacher competency development in madrasah and the management of factors shaping the madrasah communication climate in efforts to develop teacher competence. The research method used a qualitative approach, with a descriptive qualitative research type. The informants of this research are the head of madrasah and teachers of Madrasah Aliyah Amaliyah Sunggal. Secondary data sources in this research are journals, books, and articles relevant to the research focus. The overall data obtained was then analyzed using the Miles, Huberman, and Saldana data analysis model, namely: data collection steps, data condensation steps, data presentation steps, and ends with drawing conclusions. The results of the study are that the madrasah head as a leader and administrator of teacher competency development through his policies actually ultimately requires teachers to be able to contribute optimally through their performance in an effort to achieve the vision and mission of the madrasah. So it can be concluded that the process of managing teacher competency development is carried out in several stages, namely: training needs analysis conducted through communication with various parties including teachers, training planning, preparation of training materials, training implementation, and training assessment. Pencapaian visi dan misi madrasah ditentukan oleh berbagai aspek termasuk kompetensi guru. Oleh karena itu pengembangan kompetensi guru yang dikelola dengan efektif menjadi suatu hal yang logis dalam upaya mencapai visi dan misi madrasah. Pada berbagai lembaga pendidikan hingga masih mengalami kendala dalam upaya mengembangkan kompetensi guru, sehingga ini berdampak pada mutu pendidikan. Tujuan penelitian ini untuk mendeskripsikan bagaimana proses pengelolaan pengembangan kompetensi guru di madrasah serta pengelolaan faktor pembentuk iklim komunikasi madrasah pada upaya mengembangkan kompetensi guru. Metode penelitian menggunakan pendekatan kualitatif, dengan jenis penelitian kualitatif deskriptif. Informan penelitian ini adalah kepala madrasah dan guru Madrasah Aliyah Amaliyah Sunggal. Sumber data sekunder dalam penelitian ini berupa jurnal, buku, dan artikel yang relevan dengan fokus penelitian. Keseluruhan data yang didapatkan kemudian dianalisis menggunakan model analisis data Miles, Huberman, dan Saldana, yakni: langkah pengumpulan data, langkah kondensasi data, langkah menyajikan data, serta diakhiri dengan penarikan kesimpulan. Hasil penelitian yaitu kepala madrasah sebagai pemimin beserta pengelola pengembangan kompetensi guru melalui kebijakannya sebenarnya pada akhirnya menuntut para guru untuk dapat berkontribusi maksimal melalui kinerja mereka dalam upaya mencapai visi dan misi madrasah. Sehingga dapat disimpulkan Proses pengelolaan pengembangan kompetensi guru dilakukan dengan beberapa tahap, yaitu: analisis kebutuhan pelatihan yang dilakukan melalui komunikasi dengan berbagai pihak termasuk guru, perencanaan pelatihan, penyusunan bahan pelatihan, pelaksanaan pelatihan, dan penilaian pelatihan.